2022
DOI: 10.33899/ijvs.2021.130949.1899
|View full text |Cite
|
Sign up to set email alerts
|

In vivo study of Impact Transplantation Hematopoietic Progenitor Cells on Induced Cutaneous Wound Healing in Rabbits Model

Abstract: The goal of this study was to assess the effects of the Hematopoietic Progenitor Cells (HSCs) on full-thickness cutaneous wounds healing in rabbits. Twenty clinically healthy adult New Zealand White rabbits were used in this study; under aseptic technique and general anesthesia full-thickness excisional cutaneous wound; 20 mm x 20 mm were made on the back. The rabbits were randomly partitioned into two. In first group considered as control group, the wounds were treated with 3 ml of saline solution. In second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
1
2
0
1
Order By: Relevance
“…The current finding agrees with the previous studies, which reported that VEGF and neo-vascularization declined after 21 days beyond injection with BM-MSCs (52,57) and Hematopoietic Progenitor Cells (HSCs) (61). This phenomenon may be related to the decline in blood oxygen supply in the healed skin tissue.…”
Section: Discussionsupporting
confidence: 93%
“…The current finding agrees with the previous studies, which reported that VEGF and neo-vascularization declined after 21 days beyond injection with BM-MSCs (52,57) and Hematopoietic Progenitor Cells (HSCs) (61). This phenomenon may be related to the decline in blood oxygen supply in the healed skin tissue.…”
Section: Discussionsupporting
confidence: 93%
“…Por este método se obtuvieron las heridas con una distancia aproximada de 5 centímetros (cm), diseccionando las 3 capas de la piel (epidermis, dermis e hipodermis). Previo a la realización de las incisiones quirúrgicas en los conejos, ellos fueron tranquilizados con diazepam a dosis de 1 miligramo•kg -1 (mg•kg -1 ), y mezcla de clorhidrato de xilazina a dosis de 5 mg•kg -1 con clorhidrato de ketamina a dosis de 35 mg•kg -1 , administrada por vía intramuscular [29], el mantenimiento se realizó con isoflurano al 3 % con un flujo de oxigeno de 2 litros•minutos -1 (L•min -1 ) a través de mascarilla facial [27].…”
Section: Protocolo De Realización De Heridasunclassified
“…The second spin step was then performed, for the second spin 4000 rpm for 15 minutes should be just effective to help in forming soft pellets at the lower part of the glass tube. The superficial part of the plasma is mainly composing PPP (platelet-poor plasma) which should be removed, and concentrated platelets then homogenized (resuspended) in lower 1/3rd of plasma to create the PRP (17,18).…”
Section: Preparation Of Prpmentioning
confidence: 99%